PEMBERDAYAAN PEREMPUAN DALAM MANAJEMEN SUMBER DAYA MANUSIA PEMBELAJARAN BAHASA ARAB - Idah, Saidah (PSW, 2015)
The urgency of women empowerment in Arabic learning human resource management is areality that can not be refuted. The existence of women as a glorified community in dejure which turnedin de factoas an oppressed one in a patriarchal hegemonic culture must be supported by providing women empowerment in Arabic learning human resource management which includes the procurement, development and training, compensation, integration, maintenance, and separation even though the commonly portrayed in the context of Arabic learning human resource management is the dimension of the procurement, developmentand training, and compensation